The Nature of Managerial Work: An Investigation of the Work of the Audit Manager. - Wolf, Frank M. (The Accounting Review, 1981)
Abstract ABSTRACT: In this study, an exploratory analysis of the work of the audit manager was undertaken using the critical incident methodology. Eighty-eight critical requirements of managerial work were identified from a total of 582 critical incidents that were reported in a series of 69 structured interviews involving partners, managers, and senior field staff from five national and international public accounting firms in Canada. Critical task requirements were assigned to one of ten managerial roles originally identified by Mintzberg [1973] by a panel of seven judges. Analysis of the pattern with which critical incidents were reported was undertaken. Significant differences were found to exist in the pattern with which partners, managers, and field staff reported particular incidents. The role of the individual within the firm thus seemed to be associated with the character of the incident reported. When the pattern of critical incidents reported was analyzed for partners, managers, and senior field staff on a firm-by-firm basis, only the character of the incidents reported by senior field personnel seemed to be associated with their firm affiliations.